2006
DOI: 10.1097/01.brs.0000218485.96713.44
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prone Positioning Systems on Hemodynamic and Cardiac Function During Lumbar Spine Surgery: An Echocardiographic Study

Abstract: Adequate fluid replacement reduced hypotension and hemodynamic instability after prone positioning. The Jackson spine table and longitudinal bolsters had minimal effects on cardiac function, and should be considered in patients with limited cardiac reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
110
2
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(142 citation statements)
references
References 14 publications
5
110
2
16
Order By: Relevance
“…In the current study, a longitudinal bolster device that partially supports the chest and pelvis, partially compresses the abdomen, and positions the legs above the heart was used. Consistent with the results of the present study, Dharmavaram et al [8] showed that the longitudinal bolster device has a minimal effect on the cardiac performance. Toyota and Amaki [7] reported that the patient's assumption of a flat prone position and the use of a longitudinal bolster device caused no changes in the hemodynamic parameters, such as the CI, SV, and SVRI.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In the current study, a longitudinal bolster device that partially supports the chest and pelvis, partially compresses the abdomen, and positions the legs above the heart was used. Consistent with the results of the present study, Dharmavaram et al [8] showed that the longitudinal bolster device has a minimal effect on the cardiac performance. Toyota and Amaki [7] reported that the patient's assumption of a flat prone position and the use of a longitudinal bolster device caused no changes in the hemodynamic parameters, such as the CI, SV, and SVRI.…”
Section: Discussionsupporting
confidence: 82%
“…Most of the previous relevant studies showed that the SV, CI [6], and blood pressure [7,8] decrease when patients are made to assume a prone position. When a patient assumes a prone position, the arterial pressure can remain stable, but the CO usually decreases due to the reduced venous return.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] The most common abnormalities found were decreases in the cardiac index and stroke volume with preserved ejection fraction. These abnormalities are consistent with a decrease in venous return, possibly due to compression of the inferior vena cava.…”
Section: Discussionmentioning
confidence: 99%
“…Placing the patient prone was also a challenge during the management of this patient. Prone positioning has been found to decrease blood pressure and cardiac function during spine surgery however studies have found that adequate fluid replacement reduced the hypotension and hemodynamics instability in patients in prone position [10].…”
Section: Discussionmentioning
confidence: 99%